2008
DOI: 10.1186/1471-2458-8-255
|View full text |Cite
|
Sign up to set email alerts
|

Use of traditional complementary and alternative medicine for HIV patients in KwaZulu-Natal, South Africa

Abstract: Background: Traditional medicine use has been reported is common among individuals with moderate and advanced HIV disease. The aim of this cross-sectional study was to assess the use of Traditional Complementary and Alternative Medicine (TCAM) for HIV patients prior to initiating antiretroviral therapy in three public hospitals in KwaZulu-Natal, South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
123
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 39 publications
15
123
7
Order By: Relevance
“…Our findings revealed a strong belief in the possible role of CAM for HIV management, consistent with an earlier Malaysian study by Hasan et al reported 30%-100% use of CAM among PLWHA. [19] This substantial prevalence of CAM use among HIV population has also been reported elsewhere [15,29,[31][32][33][34][35], including the developed countries. [16] Remarkably, most participants believed in CAM use to complement conventional ARTs but not to replace it, and were of the opinion that the best time to use CAM is when ARTs are yet to be initiated.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our findings revealed a strong belief in the possible role of CAM for HIV management, consistent with an earlier Malaysian study by Hasan et al reported 30%-100% use of CAM among PLWHA. [19] This substantial prevalence of CAM use among HIV population has also been reported elsewhere [15,29,[31][32][33][34][35], including the developed countries. [16] Remarkably, most participants believed in CAM use to complement conventional ARTs but not to replace it, and were of the opinion that the best time to use CAM is when ARTs are yet to be initiated.…”
Section: Discussionmentioning
confidence: 79%
“…[47] In order to address this issue and to make ARTs use safer, a routine screening at the commencement of ARTs and during follow-ups is inevitable. [33] For this pharmacists as the drug experts could have a potential role and responsibility [48]; because patients' perceived lack of physicians knowledge and interests are the often found reasons for CAM non-disclosure [49]. In addition, interventions involving both physicians and patients may enhance communication of CAM use, avoid potential adverse events and drug interactions as well as could enhance ARTs adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They fear HIV testing , have a poor understanding of HIV and ART, and sometimes families choose to visit traditional healers or the church before the clinics. 9,17,19,28 If a mother tests HIV-positive her initial reactions may include anxiety, fear, disbelief and worry, and it may take her some time to accept her diagnosis. 29,30 The association of poor attendance with the mother as the primary caregiver suggests that the mother herself could be sick from HIV or struggling to accept and disclose her own status.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Poor patient experience makes it more likely that patients will seek help from traditional medicine and delay starting ART. 17 Stigma has also been associated with reduced utilisation of health services. 18 Even in settings with a high testing rate there is still much fear of the consequences of a HIVpositive result, such as the reactions of the partner and the community, as well as the implications for sickness and death.…”
Section: Introductionmentioning
confidence: 99%